2006
DOI: 10.1038/ni1424
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors T-bet and Runx3 cooperate to activate Ifng and silence Il4 in T helper type 1 cells

Abstract: Cell differentiation involves activation and silencing of lineage-specific genes. Here we show that the transcription factor Runx3 is induced in T helper type 1 (T(H)1) cells in a T-bet-dependent manner, and that both transcription factors T-bet and Runx3 are required for maximal production of interferon-gamma (IFN-gamma) and silencing of the gene encoding interleukin 4 (Il4) in T(H)1 cells. T-bet does not repress Il4 in Runx3-deficient T(H)2 cells, but coexpression of Runx3 and T-bet induces potent repression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
475
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 462 publications
(509 citation statements)
references
References 56 publications
29
475
1
4
Order By: Relevance
“…Results assessing in vitro IL-4 secretion were similar to results of the in vivo assays, namely, markedly reduced IL-4 levels were observed in iNKT cells from ThPok-deficient mice both at 2 and 24 h. However, it was noteworthy that iNKT cells from DKO mice produced more IL-4 than iNKT cells from ThPok-deficient mice, although the levels were lower than those produced by iNKT cells from Runx3-deficient and WT mice. The recovered IL-4 production in DKO mice was expected because several studies have reported an inhibitory effect of Runx3 on IL-4 expression in T cells, 33,49 suggesting a similar mechanism of action of Runx3 in iNKT cells. In accord with the findings of IL-17A secretion in response to aGalCer in vivo, the in vitro experiments indicated that ThPok disruption led to significantly higher expression of IL-17A by thymus-derived iNKT cells upon stimulation compared with iNKT cells from Runx3-deficient and WT control mice, whereas the sorted iNKT cells from DKO mice secreted less IL-17A than the iNKT cells from ThPok-deficient mice (Figure 4c).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Results assessing in vitro IL-4 secretion were similar to results of the in vivo assays, namely, markedly reduced IL-4 levels were observed in iNKT cells from ThPok-deficient mice both at 2 and 24 h. However, it was noteworthy that iNKT cells from DKO mice produced more IL-4 than iNKT cells from ThPok-deficient mice, although the levels were lower than those produced by iNKT cells from Runx3-deficient and WT mice. The recovered IL-4 production in DKO mice was expected because several studies have reported an inhibitory effect of Runx3 on IL-4 expression in T cells, 33,49 suggesting a similar mechanism of action of Runx3 in iNKT cells. In accord with the findings of IL-17A secretion in response to aGalCer in vivo, the in vitro experiments indicated that ThPok disruption led to significantly higher expression of IL-17A by thymus-derived iNKT cells upon stimulation compared with iNKT cells from Runx3-deficient and WT control mice, whereas the sorted iNKT cells from DKO mice secreted less IL-17A than the iNKT cells from ThPok-deficient mice (Figure 4c).…”
Section: Resultsmentioning
confidence: 93%
“…31,32 Furthermore, Runx3 functions to skew naive CD4 1 T cells toward the Th1 lineage, and Runx3 and T-bet interact to enhance the expression of IFN-c and silence IL-4 in Th1-type cells. 33 Moreover, Runx1 and Runx3 are both involved in IL-17 production by T regulatory cells. 34 Studies in mice have confirmed that in the absence of ThPok, CD4 1 NKT cells completely disappear and a new population of CD8 1 NKT cells emerges; thus, we sought to determine whether Runx1 and Runx3 are involved in the development of CD8 1 iNKT cells in ThPok-deficient mice and whether they play a part in the response of iNKT cells to antigen stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Moreover, IL-12 polarizes T cells into a type 1 helper T (Th1) effector cell phenotype. [25][26][27] Th1 polarization is further pronounced by IL-12 inhibiting the developmental program of type 2 helper T cells 28 and interference with the differentiation of regulatory T cells (Tregs) and Th17 cells induced by TGF-b. 29 Additionally, IL-12 programs effector T cells for optimal generation of effector memory T cells and T follicular helper cells.…”
Section: Il-12 Sensing By Innate and Adaptive Lymphocytesmentioning
confidence: 99%
“…36,37 Additionally, experiments have shown that master transcription factors form homodimers facilitating cooperative binding to DNA. 38,39 The formation of heterodimeric complexes leads to crossinhibition between master transcription factors. [40][41][42] When these biochemical properties are modelled mathematically, the resulting model includes high and low stable expression states 9,10 (see Box 1).…”
Section: Box 1 Positive Feedback Creates Attractorsmentioning
confidence: 99%